Vegetation Structure Of Orangutan Habitat In Kerangas Forest Within An Industrial Timber Plantation In Central Kalimantan - Yaya Rayadin; Hendrik Segah; Slamet Rochmadi; Nur Qomari; Muhammad Hanggito; Guruh Syurowo; Sister Sianturi; Zainul Arifin; Dhanu Pitoyo; Adinandra Azhari; Haekal Yudhistira; Firly Michdad (The Indonesian Forestry Certification Cooperation, 2026)
The persistence of orangutan populations within industrial landscapes depends heavily on the availability of natural forest patches that provide essential resources for foraging, nesting, and other daily activities. PT Industrial Forest Plantation (PT IFP) is an industrial timber concession in Central Kalimantan that lies within the distribution range of the Bornean orangutan (Pongo pygmaeus wurmbii) and is characterized by a kerangas forest (or heath forest) ecosystem. This study aimed to evaluate the quality of orangutan habitat within PT IFP by analyzing vegetation structure and composition, with particular emphasis on the availability of food and nesting tree species. Vegetation surveys were conducted in three High Conservation Value Areas (HCVAs)—Gawing, Mangkutup, and Muruy—using a line-transect plot method. Five vegetation plots measuring 20 × 100 m were established across the study sites, and all trees with a diameter at breast height (DBH) ≥ 10 cm were recorded. A total of 87 tree species belonging to 29 families were identified, with the highest species richness observed in Muruy (64 species from 24 families), followed by Mangkutup (41 species from 22 families) and Gawing (36 species from 18 families). Importance Value Index (IVI) analysis revealed that species from the families Dipterocarpaceae and Myrtaceae dominated the stand structure across all sites. Sorensen Similarity Index values among the three HCVAs ranged from 44.0% to 53.33%, indicating moderate similarity in species composition. Of the total tree species recorded, 49.43% were classified as orangutan food trees and 60.92% as nesting trees, demonstrating that kerangas forests within the concession provide key resources required by orangutans. These findings emphasize the ecological importance of kerangas forests embedded within industrial timber landscapes and highlight their critical role in supporting the persistence of Bornean orangutan populations through habitat-based conservation management.